Enhancement of Phosphorylation and Transport Activity of the Neuronal Glutamate Transporter Excitatory Amino Acid Transporter 3 by C3bot and a 26mer C3bot Peptide - Piepgras, Johannes; Rohrbeck, Astrid; Just, Ingo; Bittner, Stefan; Ahnert-Hilger, Gudrun; Höltje, Markus (Frontiers in Cellular Neuroscience, 2022)
In primary murine hippocampal neurons we investigated the regulation of EAAT3-mediated glutamate transport by the Clostridium botulinum C3 transferase C3bot and a 26mer peptide derived from full length protein. Incubation with either enzyme-competent C3bot or enzyme-deficient C3bot156-181 peptide resulted in the upregulation of glutamate uptake by up to 22% compared to untreated cells. A similar enhancement of glutamate transport was also achieved by the classical phorbol-ester-mediated activation of protein kinase C alpha (PKC). Yet comparable, effects elicited by C3 preparations seemed not to rely on PKC activation. By using biochemical and molecular biological assays we could rule out that the observed C3bot and C3bot 26mer-mediated effects solely resulted from enhanced transporter expression or translocation to the neuronal surface but was rather mediated by transporter phosphorylation at tyrosine residues that was found to be significantly enhanced following incubation with either full length protein or the 26mer C3 peptide.